Simulation and Assessment of Groundwater for Domestic and Irrigation Uses - Majed Rodhan Hussain; Basim Sh. Abed (Civil Engineering Journal, 2019)
The alluvial fan of Mandali located between latitude 30˚45’00” N longitude 45˚30’00” E in east of Diyala Governorate, Iraq. Thirty-five wells were identified in the study area with average depth of 84 m and estimated area of 21550 ha. A three-dimensional conceptual model was prepared by using GMS program. From wells cross sections, four geological layers have been identified. The hydraulic conductivity of these layers was calculated for steady state condition, where the water levels for nine wells distributed over the study area were observed at same time. Afterward, PEST facility in the GMS was used to estimate the aquifer hydraulic characteristics. Other characteristics such as storage coefficient and specific yield have been determined from one year field observations that were collected by General Authority of Groundwater, Diyala Governorate. Also, the observations were used for calibration of unsteady state model. Then wells were hypothetically redistributed and increased to 103 wells, assuming a distance of 1500 m between the wells, a well productivity rate of were 7 l/s, annual rainfall rate was used for recharging. Three different wells operating times were suggested and these 6, 12, and 18 hr/day with total discharge of 150, 300, 450 m3/day and maximum drawdown of 7, 11, and 20 m respectively. For water quality assessment, the collected groundwater samples were analysed at the laboratory.  Results showed that the TDS in all wells was ranged from 1000-3000 mg/l but TDS in well number 18 was exceeded 3000 mg/l which indicate that the groundwater in this well is not recommended to be used for irrigation. According to Iraqi standard for drink (IQS 2009), it can be used for drinking if saline treatment units were provided.